Evaluation of the effect of agroclimatic variables on the probability and timing of olive fruit fly attack - Rondoni, Gabriele; Mattioli, Elisabetta; Giannuzzi, Vito Antonio; Chierici, Elena; Betti, Andrea; Natale, Gaetano; Petacchi, Ruggero; Famiani, Franco; Natale, Antonio; Conti, Eric (Frontiers in Plant Science, 2024)
Agroclimatic variables may affect insect and plant phenology, with unpredictable effects on pest populations and crop losses. Bactrocera oleae Rossi (Diptera: Tephritidae) is a specific pest of Olea europaea plants that can cause annual economic losses of more than one billion US dollars in the Mediterranean region. In this study, we provide the first attempt to understand the effect of landscape, olive tree phenology and other agroclimatic variables on B. oleae infestation dynamics in Umbria region (Central Italy). Analyses were carried out on B. oleae infestation data collected in 79 olive groves during a seven-year period (from 2015 to 2021). In July-August, B. oleae infestation (1% attack) was negatively affected by altitude and spring mean daily temperatures, and positively by higher winter mean daily temperatures and olive tree cumulative degree days. In September-October, infestation was negatively affected by a positive soil water balance and high spring temperatures. High altitude and cumulative degree days of the plant were related to delayed attacks. In contrast, high winter and spring temperatures accelerated them. Our results could be helpful for the development of predictive models and for increasing the reliability of decision support systems currently used in olive orchards.